2012
DOI: 10.1007/s12080-012-0163-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant–soil feedbacks and the coexistence of competing plants

Abstract: Plant-soil feedbacks can have important implications for the interactions among plants. Understanding these effects is a major challenge since it is inherently difficult to measure and manipulate highly diverse soil communities. Mathematical models may advance this understanding by making the interplay of the various processes affecting plant-soil interaction explicit and by quantifying the relative importance of the factors involved. The aim of this paper is to provide a complete analysis of a pioneering plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
81
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 38 publications
1
81
1
Order By: Relevance
“…We found that plant–soil feedbacks were not related to plant community stability. This is in contrast to our final hypothesis that negative plant‐soil feedbacks increase vegetation dynamics, while positive plant–soil feedback increases vegetation stability (van der Putten and Peters 1997, Bever 2003, Revilla et al 2013). Plant communities were more stable in grazed than in ungrazed grassland plots, whereas plant–soil feedback effects were generally not different between grazing treatments (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that plant–soil feedbacks were not related to plant community stability. This is in contrast to our final hypothesis that negative plant‐soil feedbacks increase vegetation dynamics, while positive plant–soil feedback increases vegetation stability (van der Putten and Peters 1997, Bever 2003, Revilla et al 2013). Plant communities were more stable in grazed than in ungrazed grassland plots, whereas plant–soil feedback effects were generally not different between grazing treatments (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, plants will perform worse in soils where conspecific plants were abundant in the field (Mangan et al 2010). Finally, we hypothesized that spatiotemporal vegetation patterns become more dynamic if herbivores promote negative plant–soil feedback, because negative plant–soil feedback reduces the competitive ability of plants leading to increased species turnover (van der Putten and Peters 1997, Olff et al 2000, Bever 2003, Revilla et al 2013).…”
mentioning
confidence: 99%
“…Second, PSFs must be comparable in size to differences in intrinsic growth rates among species to affect rank order abundance (Petermann et al 2008, Turnbull et al 2010, Revilla et al 2013, Sun et al 2014. We suggest several reasons that relatively large PSF effects will cause relatively small improvements in predictions of plant mass in communities.…”
Section: Discussionmentioning
confidence: 96%
“…() to define an “interaction coefficient,” Is, whose sign is mathematically a necessary (but not sufficient) criterion for plant coexistence (Revilla et al. , Ke and Miki ). Bever et al.…”
Section: Modeling Plant–soil Microbe Interactionsmentioning
confidence: 99%
“…Bever () added Lotka‐Volterra‐type density‐dependent plant competition to the original frequency‐based plant–soil feedback model; Revilla et al. () later analyzed this model and derived indexes corresponding to the original Is in Bever et al. ().…”
Section: Modeling Plant–soil Microbe Interactionsmentioning
confidence: 99%